Corporate social responsibility and frontline employees’ service improvisation: The mediating role of self-efficacy - Zhang, Xuezhao; Zhang, Siyuan; Wang, Mingsen (Frontiers in Psychology, 2022)
The uncertainty of the COVID-19 pandemic has brought unprecedented challenges to frontline employees in tourism enterprises. In the context of the COVID-19 pandemic, the fulfillment of corporate social responsibility is of great significance. Based on the social cognitive theory, a conceptual framework was established to investigate the relationship between corporate social responsibility and tourism service improvisation, along with the mediating role of self-efficiency. A total of 405 self-administered questionnaires were collected through three times. The results revealed that frontline employees’ perception of corporate social responsibility had a significant positive impact on self-efficacy and service improvisation, as well as self-efficacy had a significant positive impact on service improvisation. Meanwhile, self-efficacy played a partial mediating role in the relationship between corporate social responsibility and service improvisation. Theoretical and practical implications, along with limitations and future research directions, were discussed.